Autophagy, Inflammation, and Metabolism (AIM) Center of Biomedical Research Excellence: supporting the next generation of autophagy researchers and fostering international collaborations. Issue 6 (3rd June 2018) - Deretic, Vojo; Prossnitz, Eric; Burge, Mark; Campen, Matthew J.; Cannon, Judy; Liu, Ke Jian; Sklar, Larry A.; Allers, Lee; Garcia, Sally Ann; Baehrecke, Eric H.; Behrends, Christian; Cecconi, Francesco; et al.
ABSTRACT: Recently, NIH has funded a center for autophagy research named the Autophagy, Inflammation, and Metabolism (AIM) Center of Biomedical Research Excellence, located at the University of New Mexico Health Science Center (UNM HSC), with aspirations to promote autophagy research locally, nationally, and internationally. The center has 3 major missions: (i) to support junior faculty in their endeavors to develop investigations in this area and obtain independent funding; (ii) to develop and provide technological platforms to advance autophagy research with emphasis on cellular approaches for high quality reproducible research; and (iii) to foster international collaborations through the formation of an International Council of Affiliate Members and through hosting national and international workshops and symposia. Scientifically, the AIM center is focused on autophagy and its intersections with other processes, with emphasis on both fundamental discoveries and applied translational research.